2014
DOI: 10.1186/s12879-014-0623-z
|View full text |Cite
|
Sign up to set email alerts
|

Use of simple clinical and laboratory predictors to differentiate influenza from dengue and other febrile illnesses in the emergency room

Abstract: BackgroundClinical differentiation of influenza from dengue and other febrile illnesses (OFI) is difficult, and available rapid diagnostic tests have limited sensitivity.MethodsWe conducted a retrospective study to compare clinical and laboratory findings between (i) influenza and dengue and (ii) influenza and OFI.ResultsOf 849 enrolled patients, the mean time between illness onset and hospital presentation was 1.7, 3.7, and 3 days for influenza, dengue, and OFI, respectively. Among pediatric patients (≤18 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 37 publications
(48 reference statements)
0
17
0
Order By: Relevance
“…Coryza, sore throat and cough, signs and symptoms cited by Huang et al (2014) as suggestive of other febrile illnesses such as influenza presented almost perfect to substantial agreement. Dyspnoea was an exception.…”
Section: Discussionmentioning
confidence: 75%
“…Coryza, sore throat and cough, signs and symptoms cited by Huang et al (2014) as suggestive of other febrile illnesses such as influenza presented almost perfect to substantial agreement. Dyspnoea was an exception.…”
Section: Discussionmentioning
confidence: 75%
“…We found that leukopenia was more frequent in D4 than in ND, although the overlapping range between the two groups prevented an adequate discrimination between them. The relevance of leukopenia as a discriminant feature of dengue infection has been previously documented, although the cutoff values may vary [ 13 , 31 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to findings in other studies [ 22 , 35 ], there was no significant difference in hematocrit between groups. This may be because both hemoconcentration and platelet drop are usually not seen in the first days of disease [ 34 ]. Repeated monitoring of the platelet count and hematocrit is recommended, as an abrupt fall in platelet count is proposed as a warning sign, and a significant hematocrit increase is an indirect sign of plasma leakage [ 10 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found a higher prevalence of cough, rhinorrhea and nasal congestion, in patients hospitalized for suspected dengue tested positive for influenza; this respiratory symptomatology could guide to test for influenza in those cases hospitalized for suspected dengue. This sign is described in the literature to differentiate influenza other acute febrile infections [ 17 ]. As has been described in the literature, the tourniquet test can be useful to differentiate dengue from other acute febrile illnesses [ 18 ].…”
Section: Discussionmentioning
confidence: 99%